Law and practice of legal aid in Scotland - Stoddart, Charles N. (The University of Edinburgh, 1978)
This thesis is an attempt to conduct for the first time in Scotland a comprehensive analysis of this history and practice of legal aid and advice. There is a long tradition of legal aid being provided gratuitously for poor persons by Scots lawyers, but there is no single work dealing with the development of the subject from its roots in the 15th century to the present day. The work is divided into five parts. Part I is purely historical and traces legal aid in Scotland from 1424 to present times. Parts II to V deal in detail with legal aid and advice as presently available under the Legal Aid and Advice (Scotland) Acts 1967 and 1972, and are intended primarily for the practising lawyer. Part II deals generally with legal aid administration, Part III deal3 with civil legal aid under s.1 of the Legal Aid (Scotland) Act 1967, Part IV deals with criminal legal aid, and Part V deals with legal advice and assistance. Thus, the emphasis of the work is practical, against an historical background. For example, there is no attempt to deal with the "unmet need" for legal services in Scotland, nor to probe the question of whether legal services of all types should be nationalised. Rather, the purpose of the author has been to try to satisfy another type of "unmet need"? the need for an up-to-date, properly vouched and reasoned exposition of present-day law and practice - as required by the law practitioner. The case law in Scotland is fully dealt with and the policy of the legal aid authorities in Scotland in relation to various matters is also indicated in the text.